Pemberian Abu Boiler Kelapa Sawit dan Kotoran Ayam terhadap Sifat Fisika dan Kimia Tanah pada Lahan Pascatambang Batubara - Putri Amalina Noor Thaharah; Abdul Haris; Ismed Fachruzi (Acta Solum, 2024)
The mining process can result in the mixing soil (post-coal mining soil) that tends to have low nutrient content, such as nitrogen, phosphorus, and potassium, which are crucial for plant growth. Additionally, the water flow in post-coal mining soil is often disturbed. The coal mining process can damage the soil structure and affect its ability to absorb water. The purpose of study is to examine the impact of palm boiler ash (PBA) and chicken manure fertilizer influence on soil pH, bulk density, and permeability, as well as the concentrations of total nitrogen, total phosphorus, and total potassium. The research method used a Completely Randomized Design with two factors: PBA (0 t ha-1, 5 t ha-1, 10 t ha-1) and chicken manure (0 t ha-1, 10 t ha-1, 20 t ha-1). The research findings show that applying PBA fertilizer and chicken manure impacts pH, bulk density, permeability, total nitrogen, total phosphorus, and total potassium from chicken manure. The application of 10 t ha-1 PBA and 20 t ha-1 chicken manure showed the best treatment that could increase the permeability, pH, total P and K of the soil